Risk–benefit assessment of the combined oral contraceptive pill in women with a family history of female cancer. (October 2014) - Davidson, Brittany Anne; Moorman, Patricia G
<x xml:space="preserve">Abstract</x> Introduction: Oral contraceptive pills (OCPs) are the most frequently used form of effective, reversible contraception among women of childbearing potential. In the average risk population, OCPs may offer a protective benefit against ovarian, endometrial and colorectal malignancies. In women at high risk for breast, ovarian, endometrial or colorectal malignancies, the risk–benefit profile is less well studied. Areas covered: In this article, we review pertinent literature on the use of OCPs in patients with genetic susceptibilities due to mutations in BRCA1, BRCA2 or mismatch repair genes implicated in hereditary nonpolyposis colorectal cancer as well as those with a strong family history of malignancies associated with these syndromes. Expert opinion: For women at high risk for ovarian, endometrial and/or colorectal malignancies due to genetic susceptibilities or a strong family history, the possibility of chemoprevention with OCPs may be an attractive option; however, the potential increase in breast cancer, although small, must be considered in clinical decision-making. The ultimate decision to use OCPs in a high-risk woman should be based on a consideration of her specific genetic risk, her age, her reproductive plans and her willingness to consider surgical prophylaxis options.